Pengaruh Literasi Ekonomi dan Digital Skill Terhadap Cognitive Flexibility pada Siswa Kelas XI SMA Negeri Jakarta Timur - Putri Namira Bintoro; Suparno Suparno; Fitra Dila Lestari (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The study aimed to examine the influence of economic literacy and digital skills on students' cognitive flexibility. The study employed quantitative methods. The primary data source was questionnaires distributed to eleventh-grade economics students as respondents. The data analysis technique used was the Structural Equation Model (SEM) with Partial Least Square (PLS) using the SmartPLS application. The study found that economic literacy had a positive and significant impact on cognitive flexibility. Furthermore, digital skills also had a positive and significant impact on cognitive flexibility. The results of this study indicate that the better students' economic literacy and digital skills, the greater their cognitive flexibility.